Factor Associated with Exclusive Breastfeeding at Oebobo Public Health Center in Kupang City 2023 - Radja, Angeline Miha; Sinaga, Masrida; Dodo, Dominirsep O. (Faculty of Public Health, Nusa Cendana University, 2024)
Exclusive breast milk is the process of providing breast milk within 6 months without any drinks or additional food for babies. Breastfeeding is exclusively beneficial in maintaining the health of the baby. Lack of breast milk intake causes unbalanced infant nutrition. The problem is that exclusive breastfeeding in Indonesia and the Oebobo Health Center have not reached the target. This research aims to find out what factors are related to exclusive breastfeeding at the Oebobo Health Center in 2023. This research is an analytical survey, with a cross sectional research design. The population in this study is mothers who have babies 6-7 months at the Oebobo Health Center. The sampenyal collection technique is simple random sampling and the number of sampenyal is 52 people. The data were analyzed using univariate and bivariate with chi square test. The results showed that there was a relationship between knowledge (ρ=0.002), attitude (ρ=0.002), work (ρ=0.003), family support (ρ=0.001), and health worker support (ρ=0.001). Health workers should provide a good explanation regarding exclusive breastfeeding to mothers and mothers' families since the mother checked for pregnancy, increase the frequency of counseling by utilizing various health promotion media, and guidance on breastfeeding counseling. It is hoped that mothers should also visit health facilities more regularly so that they can get information or counseling related to exclusive breastfeeding. Working mothers can seek exclusive breastfeeding by sucking milk before going to work.